Mitochondrial Dysfunction and Parkinson’s Disease—Near-Infrared Photobiomodulation as a Potential Therapeutic Strategy - Foo, Aaron Song Chuan; Soong, Tuck Wah; Yeo, Tseng Tsai; Lim, Kah-Leong (Frontiers in Aging Neuroscience, 2020)
As the main driver of energy production in eukaryotes, mitochondria are invariably implicated in disorders of cellular bioenergetics. Given that dopaminergic neurons affected in Parkinson’s disease (PD) are particularly susceptible to energy fluctuations by virtue of their high basal energy demand, it is not surprising to note that mitochondrial dysfunction has emerged as a compelling candidate underlying PD. A recent approach towards forestalling dopaminergic neurodegeneration in PD involves near-infrared (NIR) photobiomodulation (PBM), which is thought to enhance mitochondrial function of stimulated cells through augmenting the activity of cytochrome C oxidase. Notwithstanding this, our understanding of the neuroprotective mechanism of PBM remains far from complete. For example, studies focusing on the effects of PBM on gene transcription are limited, and the mechanism through which PBM exerts its effects on distant sites (i.e. its ‘abscopal effect’) remains unclear. In addition, clinical application of NIR in PD proves to be challenging. Efficacious delivery of NIR light to the substantia nigra pars compacta, the primary site of disease pathology in PD, is fraught with technical challenges. Concerted efforts focused on understanding the biological effects of PBM and improving the efficiency of intracranial NIR delivery are therefore essential for its successful clinical translation. Nonetheless, PBM represents a potential novel therapy for PD. In this review, we provide an update on the role of mitochondrial dysfunction in PD and how PBM may help mitigate the neurodegenerative process. We also discussed clinical translation aspects of this treatment modality using intracranially implanted NIR delivery devices.